A Case of Synovial Chondromatosis of Temporomandibular Joint with Numerous Loose Bodies. (11th December 2021) - Matsusue, Yumiko; Yamamoto, Kazuhiko; Yamakawa, Nobuhiro; Yamamoto, Ikumi; Matsuda, Shinpei; Yoshimura, Hitoshi; Kawakami, Tetsuji; Kirita, Tadaaki
Abstract : Here, we report a case of synovial chondromatosis of the temporomandibular joint (TMJ) with numerous loose bodies. A 56-year-old woman was examined in the oral surgery department for trismus and pain in the left TMJ when opening the mouth. Imaging indicated TMJ synovial chondromatosis, and the patient was referred to our department for further examination. Her facial features were symmetrical, and no occlusal abnormalities were found. The maximum mouth opening was 30 mm, and movement of the left mandibular condyle was restricted and accompanied by pain and joint sounds. Panoramic radiography showed deformation of the left mandibular condyle and radiopaque lesions surrounding it. Computed tomography showed numerous small granules around the left mandibular condyle, some of which were calcified. Magnetic resonance imaging showed anterior disc displacement without reduction in the left TMJ and hypointense lesions on T2-weighted images. Bone scintigraphy showed an accumulation in the area of the left TMJ. Based on the diagnosis of the left TMJ synovial chondromatosis, the lesions were removed, and plastic surgery on the mandibular condyle was performed under general anesthesia. We removed 386 white loose bodies. Histopathologically, the loose bodies were consistent with synovial chondromatosis lesions. The postoperative course was uneventful, with no recurrence or TMJ dysfunction approximately 5 years after the surgery, indicating that open surgery is the best course of intervention in such cases.